Genotype by Environment Interaction (GEI) of maize varieties resistant to maize lethal necrosis for Mid Altutides of Rwanda - Ngaboyisonga, Claver; Mahabaleswara, Suresh L.; Nizeyimana, F.; Gafishi, M.K.; Mbarushimana, J.D. (University of Ruhuna, 2022)
Maize is a leading crop in Rwandan agriculture, but its production is threatened by the outbreaks of Maize Lethal Necrosis (MLN) virus disease. The establishment of MLN artificial inoculation facility in the region where Rwanda is located has facilitated the developing MLN resistant maize genotypes. The objective of this study was to identify maize MLN resistant varieties that are high yielding and stable across environments, and to integrate them with other disease management strategies in Rwanda. Forty-one maize varieties were screened through MLN artificial inoculation facility in Naivasha, Kenya. Then, 24 of them were evaluated under natural inoculation in Karama research station, Rwanda. Twelve potential maize varieties were investigated for genotype by environment interaction in four sites at mid-altitudes in Rwanda, including Cyabayaga Karama and Bugarama, over two consecutive seasons. The study identified three maize MLN moderately resistant varieties; RHM1402, RHM1407, and RHM1409 that are high yielding and stable across environments. MLN was found to increase the incidence of ear rot, hence, raising the risks of infection with harmful mycotoxins such as aflatoxins. In order to manage the MLN disease in Rwanda, it has been advocated that the identified varieties be made available to farmers and integrated with other methods of control.